Self-activated Rh–Zr mixed oxide as a nonhazardous cocatalyst for photocatalytic hydrogen evolution. Issue 26 (22nd June 2020) - Nishino, Toshio; Saruyama, Masaki; Li, Zhanzhao; Nagatsuma, Yoshie; Nakabayashi, Mamiko; Shibata, Naoya; Yamada, Taro; Takahata, Ryo; Yamazoe, Seiji; Hisatomi, Takashi; Domen, Kazunari; Teranishi, Toshiharu
Abstract : An efficient, robust and environmentally friendly Rh–Zr mixed oxide formed though the activation of Rh–Cl–Zr–O solid efficiently functions as a HER cocatalyst on Al-doped SrTiO3 . Abstract : Efficient, robust and environmentally friendly cocatalysts for photocatalysts are important for large-scale solar hydrogen production. Herein, we demonstrate that a Rh–Zr mixed oxide is an efficient cocatalyst for hydrogen evolution. Impregnation of Zr and Rh precursors (Zr/Rh = 5 wt/wt%) formed RhZrO x cocatalyst particles on Al-doped SrTiO3, which exhibited 31× higher photocatalytic water-splitting activity than a RhO x cocatalyst. X-ray photoelectron spectroscopy proved that the dissociation of Cl − ions from preformed Rh–Cl–Zr–O solid led to formation of the active phase of RhZrO x, in which the Zr/Rh ratio was critical to high catalytic activity. Additional CoO x loading as an oxygen evolution cocatalyst further improved the activity by 120%, resulting in an apparent quantum yield of 33 (±4)% at 365 nm and a long durability of 60 h. Our discovery could help scale up photocatalytic hydrogen production.